Genome-wide analysis of transcriptome and histone modifications in Brassica napus hybrid - Ma, Meng; Zhong, Wenying; Zhang, Qing; Deng, Li; Wen, Jing; Yi, Bin; Tu, Jinxing; Fu, Tingdong; Zhao, Lun; Shen, Jinxiong (Frontiers in Plant Science, 2023)
Utilization of heterosis has largely improved the yield of many crops worldwide, but the underlying molecular mechanism of heterosis, particularly for allopolyploids, remains unclear. Here, we compared epigenome and transcriptome data of an elite hybrid and its parental lines at three assessed tissues (seedling, flower bud and silique) to explore the epigenomic basis underlying heterosis in allopolyploid B. napus. Transcriptome analysis illustrated that a small proportion of non-additive genes in hybrid compared with parents and parental expression level dominance might have a great effect on heterosis. We identified histone modification (H3K4me3 and H3K27me3) variation between parents and hybrid, most of which were resulted from the differences between parents. H3K4me3 variations were positively correlated with gene expression differences among hybrid and their parents. Further, H3K4me3 and H3K27me3 were rather stable in hybridization and mainly inherited additively in B. napus hybrid. Together, our data revealed transcriptome reprogramming and histone modification remodeling in hybrid and could serve as a valuable resource for deeper understanding of heterosis in allopolyploid crops.